Sugarcane vinasse and microalgal biomass in the production of pectin particles as an alternative soil fertilizer. (1st January 2019) - Bettani, Silvia Raquel; de Oliveira Ragazzo, Gabriel; Leal Santos, Nathalia; Kieckbusch, Theo Guenter; Gaspar Bastos, Reinaldo; Soares, Marcio Roberto; Altenhofen da Silva, Mariana
Highlights: HM pectin particles with vinasse and microalgal biomass for soil fertilization. Vinasse provided greater stability to HM pectin gel and particles. Pectin/vinasse/microalgal biomass particles as macro and micronutrients source. Novel alternative to vinasse and microalgal biomass final disposal. Potential application as alternative slow release soil fertilizer. Abstract: High methoxyl pectin was used as biopolymeric matrix to produce a novel slow release soil fertilizer added with sugarcane vinasse and lipid extracted microalgal ( Desmodesmus subspicatus ) biomass residue (LMBR). Vinasse acted as the biopolymer solvent, providing greater stability to pectin gel, and as a source of nitrogen (N), potassium (K), calcium (Ca) and magnesium (Mg). LMBR (0.5%) was considered a complementary source of N and micronutrients, copper (Cu), iron (Fe) and zinc (Zn). Compared to blank pectin particles, the particles with vinasse and LMBR showed homogeneous polymer matrix, spherical shapes, higher soluble matter release and enhanced mechanical properties. Scanning electron microscopy (SEM) and Fourier Transform Infrared Spectroscopy (FTIR) analysis indicated the incorporation of microalgal biomass and nutrients from vinasse. Higher rates of biodegradation as well as larger degree of mineralization were found over a period of 36 days for vinasse and LMBR particles. These particles exhibit good perspectives as an alternative fertilizer for agriculture applications and represent an innovative solution for vinasse and LMBR final disposal.